Physiological responses during cycling with oval chainrings (Q-Ring) and circular chainrings - Cordova, A.; Latasa, I.; Seco, J.; Villa, G.; Rodriguez-Falces, J. (Journal of Sports Science & Medicine, 2014)
The aim of this study was to compare the physiological responses of cyclists using round (C-ring) or oval (Q-ring) chainrings during an incremental test until exhaustion. Following a randomized design, fourteen male elite cyclists [age (mean ± SD): 21.1 ± 2.1 yr; VO2max: 78.5 ± 5.3 mLÂ·kg-1min-1] performed two incremental maximal tests separated by 48 h (one with C-rings, the other with Q-rings). Starting at 100 W, the workload was increased by 25 W every 3 min until volitional exhaustion. Maximal heart rate, power output and oxygen consumption were compared. Blood lactate was monitored throughout the test. After the incremental test, 4 intermittent 20-s maximal sprints with a 60-s recovery period in between were performed. Maximal isometric voluntary contractions were performed at rest and immediately after each 20-s maximal sprint, and the force and EMG RMS amplitude were recorded from the vastus medialis and vastus lateralis muscles. For the incremental exercise test, no significant differences were found in the maximal power output (P=0.12), oxygen consumption (P=0.39), and heart rate (P=0.32) between Q-rings and C-rings. Throughout the incremental test, lactate levels were comparable when using both the C-rings and Q-rings (P=0.47). During the short sprints, power output was 2.5-6.5% greater for Q-rings than for C-rings (P=0.22). The decline in EMG RMS amplitude observed during the incremental tests was comparable for Q-rings and C-rings (0.42). These findings indicate that the oval chainring design, presented here as "Q-rings", did not significantly influence the physiological response to an incremental exercise test as compared to a conventional chainring.